Coupled motions of the spine under standardized in vitro conditions: a systematic review and meta-analysis - Liebsch, Christian; Wilke, Hans-Joachim (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionCoupled motions are defined as motions outside the primary motion plane and are used for in vivo kinematic measurements as well as validation of experimental and numerical models of the spine. Owing to differences in the individual movement comforts of participants and imprecise measurement methods, previous in vivo studies have been unable to determine distinct patterns of coupled motions. The aim of this meta-analysis was to identify reproducible coupled motion patterns from in vitro studies with standardized loading conditions for each section of the spine.MethodsA systematic literature search was conducted in the PubMed, Web of Science, and Embase databases in accordance with the PRISMA guidelines to identify in vitro studies on the coupled motions of human specimens (n = 120). In a three-stage procedure, we excluded all studies except those that allowed quantitative comparability of coupled motions in the individual loading directions (n = 20). The inclusion criteria were testing the intact state, quasistatic flexibility measurements using pure moments, and specifications of the analyzed levels. The coupled motions were calculated as values relative to the primary range of motions and quantitatively evaluated via meta-analysis. The one-sample Wilcoxon signed-rank test was performed in SPSS to determine the reproducibility of the coupled motions for each segmental level.ResultsOverall, no relevant coupled motions were identified for primary flexion and extension (p > 0.05). For primary lateral bending, there was evidence for low extension and moderate-to-high ipsilateral axial rotation in the thoracic spine as well as moderate ipsilateral axial rotation in the subaxial cervical spine (p < 0.05). For primary axial rotation, there were reports on low-to-moderate contralateral lateral bending in the thoracic spine and high-to-dominant ipsilateral lateral bending in the subaxial cervical spine (p < 0.05).DiscussionThis meta-analysis of in vitro studies identified some characteristic coupled motion patterns of the spine, specifically a strong motion coupling interrelationship between lateral bending and axial rotation. More studies are required to extend and substantiate the findings of this meta-analysis. Nevertheless, this dataset is valuable for validating experimental and numerical studies of the spine as well as interpreting the coupled motion behaviors of the passive spinal structures.